LIFE AND STATE ACTIVITY OF AMIR TEMUR IN THE INTERPRETATION OF LOYS LE ROY (Scientific journal of the Fergana State University, 2024)
The article examines the coverage of the history of Amir Temur in the work of the French historian Loys Le Roy, who lived in the 16th century, entitled “On the vicissitude or variety of things in the universe”. The reflections of the French Orientalist on the life and state activities of Amir Temur were analyzed based on the sources of the Timurid period. He used comparative analysis and problem-chronological methods in the research. The opinions expressed by the French orientalist on the history of Amir Temur were studied on the basis of sources, errors and shortcomings made by him were discussed.